Risk of Dementia in Adults With ADHD: A Nationwide, Population-Based Cohort Study in Taiwan - Tzeng, Nian-Sheng; Chung, Chi-Hsiang; Lin, Fu-Huang; Yeh, Chin-Bin; Huang, San-Yuan; Lu, Ru-Band; Chang, Hsin-An; Kao, Yu-Chen; Yeh, Hui-Wen; Chiang, Wei-Shan; Chou, Yu-Ching; Tsao, Chang-Huei; et al. (My University, 2019)
Objective:This study aimed to investigate the association between adults with ADHD and the risk of developing dementia. Method: Utilizing National Health Insurance Research Database of Taiwan, ADHD patients were identified and compared with age- and gender-matched controls (1:3). Results: Of the study participants, 37 (5.48%) developed dementia compared with 81 (4.0%) in the control group. Cox proportional hazards regression analysis revealed that the study participants were more likely to develop dementia. The crude hazard ratio (HR) is 3.418 (95% confidence interval [CI] = [2.289, 5.106], p < .001), and adjusted HR is 4.008 (95% CI = [2.526, 6.361], p < .001) in risk of developing dementia after adjusted for age, gender, comorbidities, geographical area of residence, urbanization level of residence, and monthly income. Conclusion: Adults with ADHD have a 3.4-fold risk of developing dementia, and other large or national data sets should be explored to support the current findings.
Keywords: adults; ADHD adults; cohort study; dementia; National Health Insurance Research Database; Longitudinal Health Insurance Database